Sampling technique for determining cocoa pod borer (Conopormorpha cramerella) (Snellen) (Lepidoptera: gracillariidae) and cocoa pod phenology - Mohd Ali, Noorazlin (2005)
An in-depth investigation on sampling of cocoa pod bore (CPB) was carried out over a 12 month period in 2000 at Malaysia Cocoa Board Research station at Hilir Perak, Sg Sumur Perak conducted over a period of 12 months. Several components were examined. The components examined were the most reliable and efficient sampling technique, determining distribution of CPB with respect to pod phenology, determining optimum sample size to produce sampling parameters for CPB. Generally, during low population levels, the mean population densities and their relative variations were similar for all sampling techniques. However, during high population densities, mean densities and relative variations increased. This is especially for random sampling which has been found as the most reliable sampling technique. Using two aggregation models which are widely used; Taylor's Power Law (b coefficient) CPB's egg were found to be highly aggregated. In detennining optimum sample sizes, two parameters were calculated; b of Green's model and β for Kuno's model. The Green model was suitable to produce the most efficient sampling sizes during low and high population densities. During high population densities, random sampling was the most reliable with Taylor's Power Law providing the optimum coefficients for developing optimum sample sizes.